Prenatal stress and child externalizing behavior: effects of maternal perceived stress and cortisol are moderated by child sex - Fleck, Leonie; Fuchs, Anna; Sele, Silvano; Möhler, Eva; Koenig, Julian; Resch, Franz; Kaess, Michael (Child and adolescent psychiatry and mental health, 2023)
Background: Externalizing behavior problems are related to social maladjustment. Evidence indicates associations between prenatal stress and child behavioral outcomes. It remains unclear how psychological distress vs. biological correlates of stress (cortisol) differentially predict externalizing behavior, and how their effects might differ as a function of child sex. Method: 108 pregnant women from the community collected salivary cortisol and reported their perceived stress during each trimester of pregnancy. At child age 9 years (M = 9.01, SD = 0.55), 70 mothers and children reported on child behavior. Structural equation modelling was used to analyze how cortisol levels and perceived stress during pregnancy predicted current child externalizing behavior, considering the moderating effect of child sex. Results: Perceived stress predicted higher externalizing behavior in boys (β = 0.42, p = 0.009) and lower externalizing behavior in girls (β = − 0.56, p = 0.014). Cortisol predicted lower externalizing behavior in boys (β = − 0.81, p < .001) and was not related to girls’ externalizing behavior (β = 0.37, p = 0.200). Discussion/Conclusion: Prenatal stress affected externalizing behavior differently in girls vs. boys. These response patters in turn differed for indicators of psychological vs. biological maternal stress, encouraging an integrated approach. Findings indicate that perceived stress and cortisol may affect child development via different trajectories.